The Epidemiology of Myasthenia Gravis in Korea - Lee, Hyung Seok (Yonsei Med J, 2016)
PURPOSE: An epidemiological study of myasthenia gravis (MG) has not been performed in Korea. The purpose of this study was to estimate the prevalence and incidence of MG in Korea. MATERIALS AND METHODS: Health Insurance Review and Assessment (HIRA) data from 2010 to 2014 were searched for MG codes as defined by the International Classification of Diseases, 10th revision. After identifying MG cases, we estimated the prevalence and annual incidence of MG based on the HIRA database and Korean population data. RESULTS: During the study period, 10138 MG cases were identified. The prevalence of MG was 10.42 cases per 100000 people in 2010 and this increased every year to 12.99 cases per 100000 people in 2014. The average incidence of MG between 2011 and 2014 was 0.69 cases per 100000 person-years. The prevalence and incidence were higher in the older (≥50 years) age group than in the younger (<50 years) age group [prevalence: 9.26 vs. 19.24 per 100000, relative risk 2.077, 95% confidence interval (CI) 1.976-2.183, p<0.001; incidence: 0.47 vs. 1.18 per 100000, relative risk 2.490, 95% CI 2.006-3.091, p<0.001]. CONCLUSION: This study was the first nationwide population-based epidemiological study of MG in Korea. The prevalence and incidence of MG were consistent with those of previous studies. We found an increase in the prevalence of MG and a predominance of elderly MG patients.